IMPLEMENTATION OF MODELS OF INNOVATIVE LOGISTICS IN THE ACTIVITIES OF TRAVEL COMPANIES IN THE CONTEXT OF ELIMINATING THE PROBLEMS OF THEIR FUNCTIONING - Khaydarova, Nigina (IJBLE Scientific Publications Community Inc., 2022)
On articles introduction of innovative logistics models in the activities of tourist companies in the conditions of elimination of problems of their functioning in nowadays. In the study of the research, the following methods were utilized: theoretical (analysis; synthesis; specification; generalization, simulation); diagnostic (questionnaire; prediction); empirical (studying the experience of organizing the tourism activities and regulatory documentation); methods of mathematical statistics and graphical representation of the results Moreover, how can develop the formation of recreational logistics in tourism sections